2009
DOI: 10.1039/b905839g
|View full text |Cite
|
Sign up to set email alerts
|

Copper catalyzed atom transfer radical cascade reactions in the presence of free-radical diazo initiators as reducing agents

Abstract: Exceptional activity of [Cu(II)(TPMA)Cl][Cl] (TPMA = tris(2-pyridylmethyl)amine) complex in atom transfer radical addition (ATRA) of CCl(4) to 1,6-dienes followed by sequential atom transfer radical cyclization (ATRC) in the presence of free-radical diazo initiators as reducing agents is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Secondly, a better catalyst could also be a more stable catalyst, which gives rise to higher turnover numbers, or a more selective catalyst, which gives low amounts of side products. However, the fact that the rate-limiting step of ATRA reactions can be metal-independent should be considered for future studies, even more so as it is common practice to test new catalysts with intrinsically active substrates such as CCl 4 . [5] Another interesting finding of our study is the observation that a Ru III complex such as 1 can be catalytically active without prior reduction.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, a better catalyst could also be a more stable catalyst, which gives rise to higher turnover numbers, or a more selective catalyst, which gives low amounts of side products. However, the fact that the rate-limiting step of ATRA reactions can be metal-independent should be considered for future studies, even more so as it is common practice to test new catalysts with intrinsically active substrates such as CCl 4 . [5] Another interesting finding of our study is the observation that a Ru III complex such as 1 can be catalytically active without prior reduction.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…[3] Meanwhile, many transitionmetal complexes are known to promote inter-and intramolecular ATRA reactions. [1] The highest activities are typically found for copper [1,4] and ruthenium [1,[5][6][7] catalysts. One of the best catalysts described so far is the half-sandwich complex [RuCl 2 Cp*A C H T U N G T R E N N U N G (PPh 3 )] (1; Cp*= pentamethylcyclopentadienyl).…”
Section: Introductionmentioning
confidence: 98%
“…Both processes originated from well-known Kharasch addition in which polyhalogenated compounds were added to alkenes via free-radical means (13,39,40). Recent studies have also indicated that TPMA is a superior complexing ligand in ATRA (13,33,40,(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54) and ATRP (49,(55)(56)(57)(58) that utilize reducing agents. The role of a reducing agent in both systems is to continuously regenerate the activator species (copper(I) complex) from the corresponding deactivator (copper(II) complex).…”
Section: Catalysis With Transition Metal Complexes Containing Tpma LImentioning
confidence: 97%
“…For example, it is widely used as a chelator in copper and/or iron complexes that mimic certain metalloenzymes of relevance to oxygen activation (12,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Furthermore, a number of metal complexes with TPMA have also been shown to be active in C-H and O-O activation of small molecules (26)(27)(28)(29)(30)(31)(32), as well as [3+2] azide-alkyne cycloaddition (33)(34)(35)(36)(37)(38).…”
Section: Catalysis With Transition Metal Complexes Containing Tpma LImentioning
confidence: 99%
“…Radical initiators such as AIBN or V-70 (2,2 -azobis-4-methoxy-2,4-dimethyl valeronitrile) were used in catalytic amounts to reduce Cu(II) to the catalytically active Cu(I) species (eq 4). 29 Trispyrazolylborate complexes of Cu(I) catalyze the same reaction, albeit higher temperatures are required and the diastereoselectivity is lower. A plethora of protocols has been developed to introduce substituted difluoromethyl or perfluoroalkyl groups.…”
Section: T-buoh/h 2 O 96%mentioning
confidence: 99%